Framework for Establishing an Effective Management Team within Organizations - Ana Tomova; Beti Andonovic; Aleksandar T. Dimitrov (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2025)
This paper presents contemporary concepts, characteristics, and managerial strategies tailored for the demands of the new century. It delves into the significance of competitiveness and the implementation of effective management practices, emphasizing the pivotal role of knowledge management, organizational culture, and environmental analysis. The central focus lies in explaining the fundamental traits of a modern manager, highlighting the imperative for proactive improvement within the company. The subject of this paper is to evaluate the adoption of contemporary management principles by corporate management teams. The study examines the merits, drawbacks, and obstacles faced by these teams through surveys, aiming to optimize management teams. The research employs the Julie Hay's Working styles Questionnaire to predict Role distribution within working teams, offering a strategic advantage over empirical allocation. Furthermore, it utilizes the Adizes' Questionnaire to assess the development of key characteristics essential for effective decision-making within organizations. Surveys were conducted in two Macedonian companies following international research standards. Statistical analysis was conducted on the Questionnaire responses, offering not only a comprehensive evaluation and comparison of management team success across the surveyed companies, but also recommendations for improvements within the companies.
Keywords: M53; L22; L25; 330; Julie Hay's Questionnaire; Adizes' Questionnaire; team work; success criteria; management team